As sentenças judiciais e o sistema normativo recursal : desconstrução dos conceitos de juridicidade e legalidade à luz do princípio da eficiência - Jardim, Carlos Jair de Oliveira (2011)
The state is being geared to the control and centralization of society. This attitude has been perpetuated over the absolute, social and liberal state models for maintaining order and power. In absolutism the truth was identified with of the sacredness of the laws. In liberalism the truth was instrumentalized by pure worship of the rationality of the laws. In the welfare state, even with the semantic expansion, the jurisdiction and power remained correlated. In Brazil, the weak representation in political society favored to monism state that favored the face paternalistic and interventionist. With the imbalance social and expansion of social rights was an escalation in the search of legal protection for the restoration of equality. In the same in proportion that cognitive freedom of the judiciary, there was increased demand that triggered the process to discredit the basis of judicial decisions. In contrast, it is found, through statistical data, that the decisions of first instance is more propitious moment for the realization of the principles of cooperative interactions and orality, and therefore the conclusion of the dispute by conciliation procedure. Denying such a stance, there are speeches in favor of legality, which reinforces the double degree of jurisdiction as a constitutional guarantee, and therefore, unremovable, although this understanding is in misalignment franc with the normative interpretation of legal precedents. The practical result of this dissent is that systematic incursions appellate become unviable the unborn principle of efficiency. The model of the syllogism, still applicable in various situations, allowed way to juridical posture amplified and broke the barrier of absolute, assuming the plausible and reasonable. Had establish the conflict between the legality that legitimizes to appellate systematics and the legality of the efficiency and the equity. Issues such as legal defense and wider debate by appellate process commune to the detriment of those, the example of some questions concerning the procedures collegiate as "judgment-list" and also by comparison of procedural small reforms which extending the powers of judge and allowed to effectiveness of judgments. The landscape scene shows the new projection of Legal Institutions for their restoration and resizing. Jurisdiction should be as quick as possible to the truth, but the new model of fair decision is one that is more in the form of detachment from the concept of universalizing, totalizing visions, of the unity and of absolute certainties. The theme is fractal, the open, the plural. From the point of view of the microsystem legal signals to the tendency of the force of precedent. However, part of the jurisdiction, which is one, uncomfortably, has been ruled out of this process. The base jurisdiction, the accuracy of the strong stamp of legality appellate, are not incorporated as an element of composition of conflicting solutions, behold, its decisions are systematically repulsed. The contemporary juridical posture, apanage of a system of rules and criteria weighting diversified, erected by increasingly plural societies, apparently is consistent in more with this intricate cultural process whose philosophical debates travels the supposed succession between Modernity and Postmodernity